Effects of physical training programs on healthy badminton players’ performance: a systematic review and meta-analysis - Ma, Shuzhen; Xue, Weijia; Soh, Kim Geok; Liu, Huange; Xu, Fan; Sun, Min; li, Jing; Shi, Xijie; Wang, Xinzhi (BioMed Central, 2025)
Research background: Despite the abundance of common physical training programs designed for healthy badminton players, there is a significant gap in comprehensive studies evaluating their impact on player performance. Research purpose: This systematic review and meta-analysis aimed to determine the effects of common physical training programs on performance outcomes of healthy badminton players. Method: To address this gap, a meticulous search was conducted across several databases, including Scopus, PubMed, Web of Science, and EBSCOhost, up until January 2024, leading to the selection of relevant articles for a systematic review and subsequent meta-analysis using Review Manager (version 6) software. Result: The review incorporated 370 participants from 15 studies, with 12 studies qualifying for the meta-analysis. These studies commonly implemented exercise interventions ranging from 4 to 10 weeks, with participants undergoing 2 to 3 sessions weekly. The meta-analysis results showed that VO2max data indicated significantly improved performance in the experimental group (EG) (SMDb = 1.27; P = 0.0001; I2 = 0.0%) with low heterogeneity. Agility data also demonstrated significantly improved performance in the EG (SMDb = -0.61; P = 0.01; I2 = 13%) with low heterogeneity. Subgroup analysis of balance performance revealed significant improvements with different physical training programs: balance related training (effect size 5.63, p < 0.001, I2 = 35%), pilates training (effect size 2.25, p < 0.001, I2 = 78%), and core training (effect size 6.82, p < 0.001, I2 = 33%). Conclusion: This review found that high-intensity interval training and sprint interval training both improve VO2max in badminton players. High-intensity interval training, core training, strength and resistance training, and Pilates all enhance agility. Core training and lower limb resistance training help improve power. Balance training, core training, Pilates, and balance enhancement exercises contribute to better balance. Additionally, balance training improves the reactive strength index, while core training enhances smash performance. The meta-analysis indicates that current studies are more effective than traditional exercises in improving VO2max, agility, and balance. Nonetheless, further high-quality randomized controlled trials are needed to more accurately identify effective training interventions for improving performance in healthy badminton players.